Echi del passato. Il revival gotico e la ricerca dell’identità culturale negli Stati Uniti - Collin, Mélina (Studi e ricerche di storia dell'architettura, 2025)
This paper examines the paradoxical embrace of Gothic Revival architecture in 19th-century America, a period when the nation was defining itself independently from Europe. Americans adopted the medieval-inspired Gothic style despite political separation, drawing on European traditions. This architectural movement, initially rooted in Britain, France, and Germany during the Romantic period, resonated with Americans as they crafted their own cultural identity. Though predominantly Protestant, early Americans adapted the Gothic style, historically linked to Catholicism, to build both public and private structures. Gothic Revival, with its signature pointed arches, ribbed vaults, and spires, became a key architectural feature for churches, homes, and even civic institutions like museums. The design of some of America’s first museums — Museum of Fine Arts in Boston being the example here — was heavily influenced by London’s South Kensington Museum (known today as the V&A). By appropriating this distinctly European style, Americans not only sought aesthetic inspiration but also aimed to assert cultural legitimacy. The Gothic Revival allowed them to connect their national ambitions with a romanticized past, forging a unique American identity rooted in both historical continuity and forward-looking aspirations.